A taxonomic update of Takahashi’s historic collection of mealybugs (Hemiptera: Pseudococcidae) from Malaysia and Singapore - Dewi Sartiami; Watson, Gillian W.; Mohamad Roff M.N.; Idris A.B. (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2017)
Dr. Ryoichi Takahashi collected mealybugs (Hemiptera: Coccomorpha: Pseudococcidae) from Peninsular Malaysia and Singapore in 1943–1944, and mounted them in 39 permanent slide mounts using Canada balsam. The slides are deposited in the Department of Agriculture, Kuala Lumpur, Malaysia. The objective of this research was to update the identification of Takahashi’s specimens using recent taxonomic keys. Some preparations on cavity slides were re-mounted to facilitate identification. The re-mounted specimens, and those on the original slides, were re-examined and 12 species were identified. The Takahashi samples of Pseudococcus comstocki (Kuwana) and Rastrococcus mangiferae (Green) are the earliest records of these species from Peninsular Malaysia.